Implementasi Nilai Shiddiq dan Amanah dalam Pendidikan Agama Islam untuk Membangun Ukhuwah dan Lingkungan Pergaulan Positif - Niesa Amalia; Viona Putri Ramadhan; Neni Neni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic Religious Education (PAI) faces serious challenges from the crisis of integrity and trust in the digital era, which is manifested in the weakening of social solidarity (ukhuwah) and the emergence of a toxic social environment due to disinformation and fragility of commitment. This study aims to analyze and formulate an implementation model for the values ​​of Shiddiq (honesty and truth) and Amanah (trustworthiness and responsibility) in PAI, as well as to examine their role in building Ukhuwah and a Positive Social Environment among students. The method used is library research with a qualitative-analytical approach, involving a critical review of relevant scientific literature, journals, and books. The results of the study indicate that the implementation of these two prophetic values ​​must be carried out transformatively through integrated Project Based Learning (PjBL) and Problem Based Learning (PBL) methods, not merely cognitive transfer, but through real practice. The value of Shiddiq plays a central role in building trust and countering hoaxes, while Amanah ensures commitment and social responsibility, which collectively strengthen the bonds of ukhuwah. These findings imply the urgency of developing an Islamic Religious Education (PAI) curriculum that is responsive to digital ethics and strengthens teacher exemplary behavior (uswah hasanah) as a model of integrity. It is recommended that future research conduct empirical tests of the proposed implementation model to strengthen the generalizability of the findings.